The Policy Role of Bank Syariah Indonesia for MSMEs Sector in Community Economic Empowerment - Habibi, Ahmad; Utami, Pertiwi; Muzammil, Rozina; Nasor, Muhammad (Universitas Sebelas Maret, 2023)
The people's economy can be improved through the micro business sector. The issue of the role of Bank Syariah Indonesia (BSI) as a competent Islamic bank is a new hope for these business actors. Unfortunately, previous studies have not disclosed in depth the programs and policies of BSI after the merger. This study aims to determine the policy of Islamic banking toward the micro-business sector to empower the community's economy. The study was conducted on Bank Syariah Mandiri (BSM), which merged with two other large Islamic banks, Bank Rakyat Indonesia Syariah (BRI Syariah) and Bank Negara Indonesia Syariah (BNI Syariah), and became BSI. The research design used a qualitative approach with data collection techniques in interviews, observation, and documentation. BSI is a bank that collects and distributes funds to the public based on sharia principles. The findings show that BSI maintained its reputation as a competent Islamic bank in community empowerment efforts. This is evidenced by the inclusion of BSI in the Forbes list of The World's Best Banks 2021 because it has met the criteria for trust, terms and conditions, customer services, digital services, and financial advice. Although it has merged with two other Islamic banks, BSM continues to use the same system as before, except for some adjustments related to product policies regarding costs, benefits, and margin provisions by applicable regulations. Community empowerment through Micro Business products refers to Law Number 21 of 2008 concerning Islamic Banking. In its development, to support the community's economy, BSI carries out a sustainable finance agendavillage economic programs, food security, sociopreneur scholarships, and siding with MSMEs.Keywords: Bank Syariah Indonesia; policy; MSMEs